Ocular surface glycocalyx in health and disease - Martínez-Carrasco, Rafael; Sharma, Ajay (Frontiers in Cell and Developmental Biology, 2025)
The glycocalyx is a dynamic carbohydrate-enriched structure that forms a dense coating on the surface of animal cells, including those at the ocular surface. It plays a critical role in maintaining cellular functions and it has a significant influence in disease processes. At the ocular surface, glycoproteins such as mucins are essential for hydration, lubrication, and barrier protection. Proteoglycans and glycolipids contribute to cell signaling, and mediate interactions with pathogens. Alterations in the glycocalyx are implicated in a spectrum of ocular conditions, including dry eye disease, ocular allergies, infections, and systemic diseases such as Graft-versus-host disease (GVHD) and diabetes mellitus. Research has revealed alterations in mucin expression and aberrant glycosylation but many aspects of how these alterations contribute to disease processes remain poorly understood. Advancing our knowledge of glycocalyx composition and function offers valuable insights into the pathophysiology of ocular surface diseases and presents opportunities for novel glycocalyx-targeted therapeutic strategies to mitigate disease progression and enhance patient care. This review explores the current knowledge on the composition and functions of the ocular surface glycocalyx, emphasizing its implications in ocular surface disease.